Meat quality assessment in goats subjected to conscious halal slaughter and slaughter following minimal anaesthesia - Sabow, Azad Behnan; Sazili, Awis Qurni; Idrus, Zulkifli; Goh, Yong Meng; Ab Kadir, Mohd Zainal Abidin; Adeyemi, Kazeem Dauda (2015)
The study assessed the effect of conscious halal slaughter and slaughter following a minimal anaesthesia on quality of goat meat. Ten Boer cross bucks were divided into two groups and subjected to either halal slaughter without stunning (HS) or minimal anaesthesia prior to slaughter (AS). At pre-rigor, HS had significantly lower (p<0.05) muscle pH and glycogen than AS. The drip loss of HS was significantly lower (p<0.05) than that of AS. However, no significant difference was observed in the pH, glycogen content, MFI, cooking loss and colour between the treatments at 1and 7 d postmortem. In conclusion, goats slaughtered under fully consciousness and under minimal anaesthesia did not differ in physical and chemical quality of meat during the first seven days postmortem.